PERKEMBANGAN MOTORIK HALUS ANAK DI KOMUNITAS “X” - Shinta Trisnanda Dewi; Risa Dwi Meilani; Novia Novitasari; Ima Fitri Sholichah (Universitas Muhammadiyah Gresik, 2025)
Background: Fine motor skills play an important role in child development. Lack of parental stimuli and the influence of the social environment during the child's golden age can be factors of developmental delays. Community as a part of society can play a role in fulfilling these needs. Objective: This study aims to explore children's fine motor skills development in the